The Social and Economic Impact of Shrimp Pond Development by PT. Esaputlii Prakarsa Utama on the Community in Lingadan Village, Dakopamean District, Toli-Toli Regency - Aditya, Resky; Haris, Subhan; Ferianto, Fiki (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to determine the impact of shrimp farming companies on society and the environment to achieve prosperity for the community and not damage the environment. Law Article 74 Number 40 of 2007 concerning limited liability companies regulates the obligation of social and environmental responsibility in Lingadan Village. This study uses Jeremy Nicholls' theory with three indicators, namely social impact, economic impact, environmental impact. The method used in this study is a qualitative approach with a descriptive type, which collects data through interviews with related parties, including company employees and local residents of Lingadan Village. The results of the study indicate that the existence of shrimp ponds provides economic benefits for some people through employment opportunities and increased income. Social conflict also arises due to inequality of benefits and access to resources. This study recommends the need for more sustainable pond management and more intensive socialization to the community in order to minimize negative impacts and increase benefits for all residents of Lingadan Village.